Controlling Shadow IT to Ensure Data Quality in Organizations - Nurkholis, Lalu Muhammad Dzuu Mirrotin; Wibisono, Arif (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In the increasingly complex digital era, Shadow IT refers to using software, applications, or technology services without formal approval from an organization’s IT department. While it offers flexibility and fosters innovation, Shadow IT poses significant risks to data quality, potentially disrupting decision-making processes and organizational operations. This study adopts a case study approach involving multiple organizations to explore practical strategies for controlling Shadow IT to maintain data quality. Through qualitative analysis, including in-depth interviews and observations, the research identifies four key control mechanisms: incentivizing accurate reporting, ensuring data validity by relying on trustworthy sources, fostering collaborative inspections to enhance accuracy, and implementing structured policies to guide the responsible use of Shadow IT. The study also highlights two critical challenges in controlling Shadow IT: high relational trust between supervisors and subordinates and the advanced competence of staff. Although these factors may enhance efficiency, they can weaken oversight, ultimately compromising data quality. This research contributes to the information systems literature by proposing mechanisms to control Shadow IT and identifying factors undermining such control efforts.